1993
DOI: 10.1017/s0950268800050974
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology ofSalmonella typhimurium: ribosomal DNA analysis of strains from human and animal sources

Abstract: SUMMARYSalmonella typhimurium is the most frequently identified serovar of Salmonella in Italy. This serovar is characterized by the widespread dissemination among human and non-human sources of phenotypically and genetically well-differentiated clones.In this study 457 strains of S. typhimurium isolated in Italy in the years 1982-91 from human and animal sources were submitted to characterization by the rDNA fingerprinting technique. Application of this typing method, after digestion of chromosomal DNA with H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 10 publications
0
15
1
Order By: Relevance
“…However, for different Salmonella serotypes, different REs have been found to be most useful in producing interpretable ribotypes [6,9,23, 241 and the present study identified HincII alone, or in combination with SaZI and PvuII, as the most useful RE in subtyping Typhimurium. H i n d ribotyping of xx H1 S1 P1 H2 S1 P1 H3 S1 P1 H4 S1 P1 H4 S1 P4 H11 S7 P1 H3 S1 P2 H3 S2 P2 H3 S8 P2 H3 S2 Typhimurium has been reported by Nastasi et al [6]; when results from that and the present series were compared, ribotypes numbered 8, 5, 1-14, 6, 2 and 16 found by Nastasi et aZ. [6] among Italian isolates seemed identical or very similar to ribotypes H1, H3, H4, H7, H13 and HI 1, respectively, among Asturian strains.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…However, for different Salmonella serotypes, different REs have been found to be most useful in producing interpretable ribotypes [6,9,23, 241 and the present study identified HincII alone, or in combination with SaZI and PvuII, as the most useful RE in subtyping Typhimurium. H i n d ribotyping of xx H1 S1 P1 H2 S1 P1 H3 S1 P1 H4 S1 P1 H4 S1 P4 H11 S7 P1 H3 S1 P2 H3 S2 P2 H3 S8 P2 H3 S2 Typhimurium has been reported by Nastasi et al [6]; when results from that and the present series were compared, ribotypes numbered 8, 5, 1-14, 6, 2 and 16 found by Nastasi et aZ. [6] among Italian isolates seemed identical or very similar to ribotypes H1, H3, H4, H7, H13 and HI 1, respectively, among Asturian strains.…”
Section: Discussionmentioning
confidence: 60%
“…H i n d ribotyping of xx H1 S1 P1 H2 S1 P1 H3 S1 P1 H4 S1 P1 H4 S1 P4 H11 S7 P1 H3 S1 P2 H3 S2 P2 H3 S8 P2 H3 S2 Typhimurium has been reported by Nastasi et al [6]; when results from that and the present series were compared, ribotypes numbered 8, 5, 1-14, 6, 2 and 16 found by Nastasi et aZ. [6] among Italian isolates seemed identical or very similar to ribotypes H1, H3, H4, H7, H13 and HI 1, respectively, among Asturian strains. It should be pointed out, however, that the rates of the most frequent ribotypes in the two series were different.…”
Section: Discussionmentioning
confidence: 89%
“…The MIC values were so homogeneous that it appeared as if replicates of a single clonal strain had been tested. Using a rDNA fingerprinting technique, Nastasi et al (1993) found that pigeon strains belong to clones of serotype Typhimurium that are only sporadically found in humans and other animals. The isolation of the same serotypes in humans, pigeons and other animals therefore does not imply that epidemiologically related Salmonella strains are involved.…”
Section: Discussionmentioning
confidence: 99%
“…Since the serological variant Copenhagen is also responsible for sporadic cases of disease in humans and other mammals, there was considerable concern in the first half of the 20th century that pigeons may be a reservoir for salmonellosis in mammalian species. However, subsequent studies have shown that serotype Typhimurium isolates from pigeons differ in their biotype and ribotype from those isolated from humans or other animals, suggesting that pigeons are not a source of infection for other host reservoirs (46,55,65,69). Based on these data, the existence of a serotype Typhimurium "pigeon type" that predominates in pigeons but is rarely transmitted to other host species has been proposed (25,31,35,38).…”
Section: The Pigeon-adapted Variant Of Serotype Typhimuriummentioning
confidence: 99%